Role of Type 1 Diabetes–Associated SNPs on Autoantibody Positivity in the Type 1 Diabetes Genetics Consortium: Overview - Rich, Stephen S. (Diabetes Care, 2015)
OBJECTIVE: Type 1 diabetes (T1D) arises from the autoimmune destruction of the β-cells of the pancreas, resulting in dependence on exogenously administered insulin for survival. Key biomarkers of the autoimmune process in T1D are the occurrence of autoantibodies directed against β-cells and other antigens. The Type 1 Diabetes Genetics Consortium (T1DGC) assembled collections to 1) discover genes that modify the risk of T1D, 2) conduct phenotyping related to risk, and 3) make available biologic and genetic resources for research. The goal of the T1DGC Autoantibody Workshop was to use T1DGC phenotypic, genotypic, and autoantibody data on affected sibling pair (ASP) families to discover genes accounting for variation in presence of autoantibodies. RESEARCH DESIGN AND METHODS: The T1DGC provided the working groups with autoantibody and genetic data on 9,976 subjects from 2,321 ASP families. Data were distributed to numerous working groups for analyses of specific autoantibody subsets and targets. RESULTS: Seven groups analyzed the joint autoantibody and genetic data within the ASP families. Six reports are provided in this collection, ranging from candidate gene analyses of selected autoantibodies to evaluation of regions of genetic variants associated with autoimmunity on the collection of autoantibodies. CONCLUSIONS: Although selected variants in the available genes remain important genetic predictors for prevalence of T1D, other genes and nongenetic factors are expected to contribute to the initiation of islet autoimmunity, the first step in the pathogenesis of T1D.